Pengurusan risiko bekalan tenaga elektrik di bangunan tinggi : kajian kes : Bangunan Menara Maxis, Kuala Lumpur - Abu Bakar, Azmi (2004)
Lately Facilities Management has been accepted as an important section in the organization not merely as a supporting department . For those Professional Practitioners of Facilities Management require an extensive and sound knowledge in today building technology , with the awareness of the risk management come into the spectrum , the demand of facilities management services has increased . Initially managing risk is just a normal procedure in any organization but it was now became a tool that assist the management to make their decision . This research was conducted to further create the awareness of the importance of the risk management in building power supply . The objectives are to identify the existence of the risk , identify the level of risk and provide the mitigation steps . In this aspect the usage of risk metric is required , at the end of the day the findings are very much benefit to the organization .